The Comparison of Peter Parker’s Language Styles and Style-Shifting Occurrences in Jon Watts’ Spider- Man: Homecoming (2017) and Spider-Man: No Way Home (2021) Movies - Zulhelmi, Mutiara Luthfiyanti; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
This study analyzes the language style and style-shifting in Peter Parker's conversations in two movies directed by Jon Watts: Spider-Man: Homecoming (2017) and Spider-Man: No Way Home (2021). A descriptive-qualitative method was used to analyze the data. This study found that the casual language style is the most dominant in both movies. This is related to Joos' (1967)